Influence of Fiber Orientation on Impact Resistance Behavior of Woven Sisal Fiber Reinforced Polyester Composite - Genetu A. Dress; M. H. Woldemariam; D. T. Redda (Advances in Materials Science and Engineering)
Woven natural fiber reinforced polymer composites have better tensile, flexural, and compressive strength compared to the mechanical properties of unidirectional and randomly oriented NFRPC because of the interlacing of fiber bundles. However, the characterization of impact behavior with different fiber orientation such as 30°/60°, 0/90°, 30°/−45°, and 45°/−45° woven sisal fiber reinforced polyester composite was not studied vigorously. Thus, this paper focuses on the experimental characterization of the impact resistance behavior on woven sisal fiber reinforced polyester composite materials for semistructural part by using Izod impact testing setup. The 30°/60°, 30°/−45°, 0°/90°, and 45°/−45° woven sisal fiber was prepared using nailed wooden frame as a warp and weft guider. The woven sisal fiber was impregnated in order to make woven sisal fiber dimensionally stable. Using 40% by weight of fiber and 60% by weight of polyester, the composite was developed using hand layup process. The morphology and cross-sectional elemental detection was carried out using scanning electron microscope (SEM) assessment in leather development institute (LDI). Finally, impact tests were carried out using Izod impact testing setup in Addis Ababa Science and Technology University (ASTU). The average impact strength of a 40 wt% fiber 45°/−45° woven sisal fiber reinforced unsaturated polyester composite (WSFRPC) test specimen with consecutive warp and weft tow spacing of 2 mm was 342.67 J/m and this was greater energy compared to the other orientations. But the average impact strength of a 40 wt% fiber 30°/60° WSFRPC of test specimen with consecutive warp and weft tow spacing of 2 mm was 241.33 J/m.